Literal, metaphorical, and fictive motion in Italian proverbs: the influence of Path and Manner semantic components - Florio, Nicola (Romanica Olomucensia, 2025)
The purpose of this paper is to present a corpus-based study carried out to analyse the expression of motion in the Italian language through the compilation of Italian proverbs gathered by Lapucci in his Dizionario dei proverbi italiani, aiming to examine the influence of Path and Manner semantic components conflated in the verbs for the description of literal, metaphorical, and fictive motion. Based on a Corpus Linguistics approach, for this study more than 25,000 Italian proverbs were analysed, and only those containing motion verbs were selected. More than 2,000 Italian proverbs were identified and classified according to their main motion verb and then grouped by the type of motion expressed and the semantic components conflated in the verb root. The compilation of Italian proverbs was studied in depth in order to obtain statistical data about the frequency of use of each motion verb, semantic variety in terms of different types of motion expressed, the semantic components conflated in the verb root, and the productivity of each verb for the construction of literal, metaphorical, or fictive motion events. The extensive study that was carried out confirms that the Italian language offers a wide variety of motion verbs that include not only details about Path but also about the Manner in which motion is performed, and the data that was collected suggests that the semantic components of Path and Manner conflated in the verb root play a relevant role in literal, metaphorical, and fictive motion expressed in Italian proverbs.
Keywords: Italian; proverbs; motion; lexicalisation; Path; Manner